Africorchestia a new genus of sand-hoppers (Crustacea: Amphipoda: Talitridae) from western Africa and south-western Europe - Lowry, James K.; Coleman, Charles Oliver (Zootaxa, 2011)
Africorchestia, a new genus of coastal sand-hoppers (Amphipoda, Talitridae), is described from western Africa and south-western Europe. Africorchestia includes five species: A. fischeri (H. Milne Edwards, 1830); A. quadrispinosa (K.H. Barnard, 1916); A. skoogi (Stebbing, 1922); A. spinifera (Mateus, 1962); and A. tricornuta (Shoemaker, 1920).